Alveolar bone graft with Platelet Rich Plasma in cleft alveolus - Chandan Gupta; Divya Mehrotra; Shadab Mohammad; Vaibhav Khanna; Gulshan Kumar Singh; Geeta Singh; Arul A.L. Chellappa; Deepak Passi (Elsevier, 2013)
Introduction: Cleft of the lip, palate and alveolus are the commonest congenital anomaly to affect the orofacial region. Currently, there is great interest in the alveolar bone grafting procedures that involve use of platelet-rich-plasma (PRP), to enhance bone formation and specifically to promote bone graft healing. Materials and methods: 20 patients with residual alveolar cleft, in the age group of 9-29 years, having unilateral or bilateral cleft lip and palate were selected. They were randomly assigned in either group A (with PRP) or group B (without PRP). Results: Primary healing was observed in 90% patients in group A. Secondary healing was seen in 30% patients in group B. There was no graft rejection in group A but was seen in one patient (10%) in group B. Pain and swelling persisted longer in group B then group A. Bone grafts with added PRP presented with increased bone density (1028.00 ± 11.30 HU) in comparison to grafts without PRP (859.50 ± 27.73 HU) at end of 6-month postoperative. However, the mean bone density (as determined by the Dentascan image analyzer software) was 1.04 times more in the PRP group than non PRP group at 3-month and 1.2 times more at 6 months. Conclusion: We conclude that on preliminary investigations, PRP seems to enhance bone formation in alveolar clefts when admixed with autologous cancellous bone harvested from the iliac crest.